Determining Promotional Package Recommendations Using the Frequent Pattern Growth Algorithm at The Java Cafe - Astuti, Dwi; Samsinar, Samsinar (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
Data analysis and processing is very important to support business development. One example is The Javanese Café which requires analysis and processing to determine promotional menu package recommendations. To carry out data analysis and processing, of course you need technology to make these activities easier. The technology that can be used to overcome this problem is data mining. Data mining has an association rule method which functions to form association patterns. Researchers also use the FP-Growth algorithm to speed up the data processing process. The sales transaction data processing resulted in 14 association patterns with the highest confidence values and 9 menu items with the lowest support values. Then the results were analyzed again and produced 4 recommendations for promotional menu packages that could be used to support product marketing strategies.